An Overview of Coastal Waste Sources in Indonesia: A Review - Pebriyanto Setiawan; Wa Janarian Rumbia (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Waste is a byproduct of various human activities that can lead to environmental pollution, particularly in coastal areas. Improper waste management in coastal zones contributes to significant environmental degradation, affecting both public health and marine ecosystems. This literature review examines the sources of waste in coastal areas, including household waste, industrial waste, and tourism-related waste, and explores their impacts on coastal communities and ecosystems. Objective: This study aims to review scientific articles related to the sources of waste in coastal areas of Indonesia, focusing on identifying the dominant factors contributing to coastal waste pollution. Methods: A Systematic Literature Review (SLR) was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The literature search targeted articles published between 2016 and 2025, using the keyword